Overexpression of glutathione transferase E7 in Drosophila differentially impacts toxicity of organic isothiocyanates in males and females. - Aslam M A Mazari (Public Library of Science (PLoS), 2014)
Organic isothiocyanates (ITCs) are allelochemicals produced by plants in order to combat insects and other herbivores. The compounds are toxic electrophiles that can be inactivated and conjugated with intracellular glutathione in reactions catalyzed by glutathione transferases (GSTs). The Drosophila melanogaster GSTE7 was heterologously expressed in Escherichia coli and purified for functional studies. The enzyme showed high catalytic activity with various isothiocyanates including phenethyl isothiocyanate (PEITC) and allyl isothiocyanate (AITC), which in millimolar dietary concentrations conferred toxicity to adult D. melanogaster leading to death or a shortened life-span of the flies. In situ hybridization revealed a maternal contribution of GSTE7 transcripts to embryos, and strongest zygotic expression in the digestive tract. Transgenesis involving the GSTE7 gene controlled by an actin promoter produced viable flies expressing the GSTE7 transcript ubiquitously. Transgenic females show a significantly increased survival when subjected to the same PEITC treatment as the wild-type flies. By contrast, transgenic male flies show a significantly lower survival rate. Oviposition activity was enhanced in transgenic flies. The effect was significant in transgenic females reared in the absence of ITCs as well as in the presence of 0.15 mM PEITC or 1 mM AITC. Thus the GSTE7 transgene elicits responses to exposure to ITC allelochemicals which differentially affect life-span and fecundity of male and female flies.